Dis-membering and Re-membering: The Eucharist and the Suffering of Women - Loumagne, Megan (Lumen et Vita, 2014)
God desires wholeness for humanity, as well as freedom from all that dehumanizes and degrades. The Church represents the historical mediation of God’s healing presence to the world, and as such, it stands in opposition against all that enslaves humanity. The Eucharist, in particular, is a salve to the suffering of human persons. Additionally, in its expression of embodiment and relationality, the Eucharist has special relevance for women. Yet the feelings of hope and comfort found in the ritual of the Eucharist are, for many women, diminished by other feelings of alienation and isolation invoked by this ritual. Thus the Eucharist exists as a source of contradiction and tension for many Catholic women, and to the extent that the ritual celebration of the Eucharist perpetuates the dehumanization of women, it obfuscates the good news of the gospel and presents an area of needed conversion within the Church. The purpose of this paper is to draw from the resources of both sacramental theology and theological anthropology to explore the relationship between the Eucharist and the suffering of women. It is only by listening attentively to the world, and especially to those who have suffered from the world’s injustices, that the Church will be able to provide credible hope for humanity.